Profile of Comorbidities and Length of Hospital Stay Among Stroke Patient at Dr. Gunawan Mangunkusumo Hospital Semarang Regency - Sudrisman Sudrisman; Bagoes Widjanarko; Antono Suryoputro (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Stroke remains a leading cause of morbidity and hospitalization worldwide. Comorbid conditions can significantly influence the length of stay (LOS) among stroke patients. As a catastrophic disease requiring prolong and costly medical care, stroke demands optimized hospital services through strengthened resource capacity, management and referral systems. This study aims to analyze the comorbidity profile of stroke patients and its association with prolonged LOS. A retrospective analytical design was applied, reviewing medical records of all new stroke inpatients at Dr. Gunawan Mangunkusumo Regional General Hospital between January and June 2025, (n = 404). Data were collected using structured research sheets and analyzed with univariate descriptive statistics, chi-square tests, and multivariate and multivariate logistic regression to identify factors associated with prolonged LOS. Among 404 patients, 26 (6.4%) experienced extended hospitalization. Significant factors associated with prolonged LOS included a history of hypertension (p = 0.038) and coronary heart disease (p = 0.037). Coronary heart disease emerged as the strongest predictor of prolonged LOS (OR = 0.192; 95% CI: 0.068–0.539; p = 0.002), highlighting its impact on inpatient management and discharge processes. These findings suggest that integrated cardiovascular and stroke care may improve hospital efficiency. Future prospective studies incorporating measures of stroke severity are recommended. Keywords: Stroke, Length of Hospitalization, Comorbidity, Patients, Indonesia